(untitled) (Journal of Biochemistry, Microbiology and Biotechnology, 2022)
Lignin is a complex polymer class formed from the cell wall, it is an organic polymer with a variety of biological aspects and industrial applications. Deep eutectic solvent (DES) has been introduced as a green solvent to dissolve lignin from lignocellulosic biomass. DESs typically have low vapor pressure, high heat stability, low toxicity and biodegradation which are the ideal features for lignocellulosic biomass pre-treatment. In this work, Conductor-like Screening Model for Real Solvents (COSMO-RS) was used to determine the suitable DESs for lignin degradation. The performance of the selected DESs was tested on lignin monomeric compounds, commercial lignin and the actual biomass of oil palm empty fruit bunch (OPEFB). Three DESs were used to test its lignin dissolution capability, i.e. choline chloride:urea (ChCl:Ur) (1:2), choline chloride:glycerol (ChCl:Gly) (1:2) and choline chloride:glucose ( ChCl:Glu) (1:1). The saturation points of dissolving each lignin type were determined for each DES. It was experimentally found that ChCl:Ur (1:2) could dissolve more lignin than ChCl:Gly (1:2) and ChCl:Glu (1:1). This work shows the possibility of using DES to dissolve lignin structures for biomass pretreatment and utilization.